Comparison of passive ultrasonic and sonically activated irrigation methods: an investigation based on PGE2, NO and IL-6 levels - Seyda Ersahan; Fatih Ozcelik; Sertan Fındıkçı; Yelda Erdem Hepsenoglu; Duygu Degirmencioglu; Aslı Usta (BMC Oral Health)
Abstract The effectiveness of Passive Ultrasonic Irrigation(PUI) and Sonically Activated Irrigation(SAI) techniques was investigated in apical periodontitis(AP) patients based on changes in prostaglandin E2(PGE2), nitric oxide(NO), and interleukin-6(IL-6) levels. Sixty-six AP patients and thirty healthy controls were enrolled. Preoperative gingival crevicular fluid(preGCF) PGE2, NO and IL-6 levels were measured before treatment. After chemo-mechanical preparation, teeth were assigned into two groups according to final irrigation protocol[PUI(n:33) and SAI(n:33)]. The same markers were again measured 1 week after treatment(postGCF) and also 1st order most commonly seen bacteria(FMCB) typing was performed on microbial samples of the patients. PostGCF-PGE2 levels of the PUI group were lower than postGCF-PGE2 levels of the SAI group(p = 0.0335). Both postGCF-PE2 and IL-6 levels of the PUI group were significantly decreased after treatment(p < 0.0001), while only postGCF-PE2 levels decreased in the SAI group(p = 0.0316). The PUI system significantly reduced PGE2 and IL-6 levels by better controlling inflammation in the treatment of AP.